2010
DOI: 10.1182/blood-2009-07-233049
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profiling–based dissection of MLL translocated and MLL germline acute lymphoblastic leukemia in infants

Abstract: Acute lymphoblastic leukemia (ALL) in infants (< 1 year) is characterized by a poor prognosis and a high incidence of MLL translocations. Several studies demonstrated the unique gene expression profile associated with MLL-rearranged ALL, but generally small cohorts were analyzed as uniform patient groups regardless of the type of MLL translocation, whereas the analysis of translocationnegative infant ALL remained unacknowledged. Here we generated and analyzed primary infant ALL expression profiles (n ‫؍‬ 73) t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
171
0
6

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(188 citation statements)
references
References 34 publications
11
171
0
6
Order By: Relevance
“…13,[62][63][64] However, our laboratory showed that within MLL-rearranged infant ALL each type of MLL translocation is associated with a translocation-specific gene expression signature. 65 We identified a specific gene expression signature for the total group of MLL-rearranged AML cases, 12 but were also able to identify a specific signature for t(9;11)(p22;q23). 66 This indicates that, in addition to the common pathways in MLLrearranged AML, there are other pathways, which seem to be more dependent on the fusion partner of MLL.…”
Section: Epidemiology Of Mll Aberrations In Pediatric Amlmentioning
confidence: 88%
“…13,[62][63][64] However, our laboratory showed that within MLL-rearranged infant ALL each type of MLL translocation is associated with a translocation-specific gene expression signature. 65 We identified a specific gene expression signature for the total group of MLL-rearranged AML cases, 12 but were also able to identify a specific signature for t(9;11)(p22;q23). 66 This indicates that, in addition to the common pathways in MLLrearranged AML, there are other pathways, which seem to be more dependent on the fusion partner of MLL.…”
Section: Epidemiology Of Mll Aberrations In Pediatric Amlmentioning
confidence: 88%
“…The existence of two distinct subgroups among t(4;11)-positive infant ALL cases characterized by the absence or presence of HOXA expression, and that patients lacking HOXA gene expression are at high risk of disease relapse were reported. 34 Future work should be conducted to determine whether there is any biochemical link between HOXA and FLT3 gene expression, and to decipher whether MLL-AF4 þ ALL patients at extremely high risk of relapse and very short OS represent the same cohort displaying high-level FLT3 and lacking HOXA expression, thus providing important novel Abbreviations: B-ALL, B-acute lymphoblastic leukemia; BM, bone marrow; DFS, disease-free survival; FLT3, FMS-related tyrosine kinase-3; OS, overall survival; PB, peripheral blood; WBC, white blood cell. a Variables were dichotomized based on the median value.…”
Section: Discussionmentioning
confidence: 99%
“…9 Recently, however, we published high-resolution gene-expression profiling data on a larger cohort of infant ALL samples, which even allowed specification of differential gene expression between distinct subtypes of infant ALL. 11 Studying these profiles, we observed that MLL-rearranged infant ALL frequently displays high-level expression of genes encoding members of the S100 protein family. For example, S100A10 and S100A4 appeared in the top50 of over-expressed genes in MLLrearranged infant ALL when compared with non-infant pediatric precursor B-ALL.…”
Section: Introductionmentioning
confidence: 95%
“…23,24 A detailed description of the processing of RNA samples and the generation of the gene expression profiles are previously described elsewhere. 11 Gene-set enrichment analysis 25 was used to evaluate enrichment of genes encoding S100 protein family members in prednisolone-resistant MLL-rearranged infant ALL samples. Supplementary Table 1 lists the gene enrichment scores for all S100 family members.…”
Section: In Vitro Prednisolone and In Vivo Prednisone Responsementioning
confidence: 99%
See 1 more Smart Citation